Peer mentoring at the Universidad Europea de Madrid: An educational strategy for the development of general and specific competences - Paloma Velasco Quintana; Agueda Benito Capa (Laureate Education Inc, 2011)
The current educational model for the Europea Higher Education Area (EHEA), demands a greater involvement on the behalf of students in all aspects of their education. In this respect, peer mentorship not only provides effective orientation for newly admitted students, a key element of quality in education, but also the active participation of students mentors, leading to the development of a wide range of skills in both mentor and mentee students. From a research-action perspective, this article describes a program of peer mentoring, in which the student interaction taking place leads to wide-ranging knowledge acquisition (knowledge and know how) for both participants. Within the sphere of mathematics, the program was developed with the aim of developing general skills, as well as the specific objective of improving competence in mathematics. In the results obtained, the profile and educational development of the student mentor, together with the study of the needs of first year students, from the perspective of teachers and students, were especially relevant. The conclusions and recommendations from this study may constitute a good basis upon which future peer mentorship programs may be developed as an approach that is very much in line with the EHEA and of great educational value. ------ La mentoría entre iguales en la Universidad Europea de Madrid: Una estrategia educativa para el desarrollo de competencias generales y específicas Resumen El modelo educativo actual, desarrollado dentro del Espacio Europeo de Educación Superior (EEES), requiere de una mayor implicación por parte de los estudiantes en todos los aspectos de su formación. En este sentido, la tutoría entre iguales no sólo proporciona una orientación efectiva de los alumnos de reciente incorporación en la universidad, elemento clave de calidad, sino una participación activa del estudiante mentor, que resulta en el desarrollo de un amplio abanico de competencias por parte de ambos (estudiante mentorizado y mentor). Este trabajo describe, desde el ámbito de la investigación-acción, un programa de tutoría entre iguales en el que la interacción que se produce en las sesiones de mentoría constituye un interesante medio de adquisición del conocimiento en sentido amplio (saber y saber hacer) para ambos participantes. El programa se desarrolla en el seno de la asignatura de Matemáticas, por lo que se busca la mejora de diversas competencias generales y, como elemento diferenciador,  un mayor desarrollo de la competencia matemática. En la presentación de resultados resulta especialmente relevante la figura del alumno mentor, su perfil y avance formativo, así como el estudio de las necesidades de los alumnos de primer curso a través de la óptica de los docentes y de los discentes. Las conclusiones y recomendaciones podrían constituir una buena base para el desarrollo de futuros programas de tutoría entre iguales, un ingrediente educativo de máxima coherencia con el EEES y de gran valor formativo. DOI: 10.18870/hlrc.v1i1.32   PDF document contains both the original in Spanish and an English translation.